Pd‐Catalyzed Annulation of 1‐Halo‐8‐arylnaphthalenes and Alkynes Leading to Heptagon‐Embedded Aromatic Systems. Issue 40 (27th December 2018) - Yan, Jianming; Rahman, Md. Shafiqur; Yoshikai, Naohiko
Abstract: A palladium‐catalyzed heptagon‐forming annulation reaction between 1‐halo‐8‐arylnaphthalene and diarylacetylene is reported. The reaction is promoted using a catalytic system comprised of Pd(OAc)2, moderately electron‐deficient triarylphosphine P(4‐ClC6 H4 )3, and Ag2 CO3 to afford benzo[4, 5]cyclohepta[1, 2, 3‐ de ]naphthalene derivatives in moderate to good yields, in preference to fluoranthene as a competing byproduct. Twofold annulation can also be achieved to access a novel heptagon‐embedded polycyclic aromatic hydrocarbon compound. Abstract : Polycyclic aromatic hydrocarbons : A palladium‐catalyzed annulation reaction between 1‐halo‐8‐arylnaphthalene and diarylalkyne is reported. Using a moderately electron‐poor triarylphosphine, the reaction takes place in preference to fluoranthene formation, affording benzo[4, 5]cyclohepta[1, 2, 3‐ de ]naphthalene derivatives in moderate to good yields. Twofold annulation is also achieved to access a novel heptagon‐embedded polycyclic aromatic hydrocarbon (see scheme).